2014
DOI: 10.1371/journal.pone.0107062
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Leaf Roughness, Surface Free Energy and Work of Adhesion on Leaf Water Drop Adhesion

Abstract: The adhesion of water droplets to leaves is important in controlling rainfall interception, and affects a variety of hydrological processes. Leaf water drop adhesion (hereinafter, adhesion) depends not only on droplet formulation and parameters but also on the physical (leaf roughness) and physico-chemical (surface free energy, its components, and work-of-adhesion) properties of the leaf surface. We selected 60 plant species from Shaanxi Province, NW China, as experimental materials with the goal of gaining in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 38 publications
1
92
1
3
Order By: Relevance
“…Leaf or plant samples were stored in a portable cool box and were immediately transported to the laboratory and kept in a freezer at 4°C, before all the measurements were completed within 2 days after sampling (Wang, Shi, et al, 2013;Wang, Shi, Li, & Wang, 2014). Leaf or plant samples were stored in a portable cool box and were immediately transported to the laboratory and kept in a freezer at 4°C, before all the measurements were completed within 2 days after sampling (Wang, Shi, et al, 2013;Wang, Shi, Li, & Wang, 2014).…”
Section: Plant Species and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaf or plant samples were stored in a portable cool box and were immediately transported to the laboratory and kept in a freezer at 4°C, before all the measurements were completed within 2 days after sampling (Wang, Shi, et al, 2013;Wang, Shi, Li, & Wang, 2014). Leaf or plant samples were stored in a portable cool box and were immediately transported to the laboratory and kept in a freezer at 4°C, before all the measurements were completed within 2 days after sampling (Wang, Shi, et al, 2013;Wang, Shi, Li, & Wang, 2014).…”
Section: Plant Species and Samplingmentioning
confidence: 99%
“…Similarly, the leaf surface retention of Ulmus pumila was found to be 60% greater than that of Catalpa speciosa, and the adaxial contact angles of Catalpa speciosa was more than double the Ulmus pumila at the same time (Holder, 2012). The plant traits considered did not include some leaf surface properties such as water droplet retention, leaf roughness, or surface free energy (Wang et al, 2014). However, the correlation was not statistically significant (p > 0.05), and the relationship between leaf hydrophobicity with individual plant surface retention were not compared.…”
Section: Relationships Between Leaf Wettability and Surface Water Rmentioning
confidence: 99%
“…Another property of the leaf surface which affects water redistribution is the adhesion of water to the leaf surface which can also contribute to self-purification processes, an important factor in inundated areas. A parameter found to be positively correlated with adhesion forces is the surface free energy (SFE) (Wang et al 2014). Plant leaves characterized by high SFE hold water droplets to their surface.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2014) observed that convex epidermal cells with wax crystals of Cynanchum chinense and Anemone vitifolia had higher CAs than leaves with smooth epidermal cells of Populus simonii and Cynanchum komarovii.…”
Section: Discussionmentioning
confidence: 92%
“…The cuticular waxes vary considerably between and among different species. Cuticular waxes change during leaf developmental stages and between leaf sides (Wang et al 2013(Wang et al , 2014(Wang et al , 2015. The CAs of Nelumbo nucifera and Colocasia esculenta were significantly lower than 90° when the wax was removed with acetone from the leaf surface by Burton and Bhushan (2006).…”
Section: Discussionmentioning
confidence: 99%